Secular variations in magmatism during a continental arc to post-arc transition: Plio-Pleistocene volcanism in the Lake Tahoe/Truckee area, Northern Sierra Nevada, California - Cousens, B; Henry, C; Harvey, B; Brownrigg, T; Prytulak, J; Allan, J (2011)
In the Lake Tahoe-Truckee River area of northeastern California, a suite of latest Pliocene to Pleistocene volcanic rocks, termed the Tahoe-Truckee volcanic field (TTVF), overlies Miocene to Pliocene volcanic rocks of the Ancestral Cascades arc. The lavas post-date the passage of the south edge of the subducting Juan de Fuca plate, and represent a secular transition from continental arc to post-arc volcanism associated with a slab window. Compared to the older arc volcanic rocks, TTVF lavas are small in volume, non-porphyritic, and mildly alkaline. TTVF lavas have a subduction signature in primitive mantle-normalized plots but, compared to the older arc rocks, are enriched in the light rare earth elements, Nb, and Ta, and depleted in the large ion lithophile elements. Isotopically, TTVF rocks overlap with Ancestral Cascade arc lavas, although most TTVF rocks fall at the high 87Sr/86Sr-low 143Nd/144Nd end of the range of Ancestral Cascade compositions. Pb and oxygen isotope ratios overlap completely. Although the incompatible element systematics are consistent with increased importance of a within-plate mantle source component in the TTVF, the more radiogenic Sr and less radiogenic Nd isotopic compositions are not and require a source that is old. We propose that, like the Ancestral Cascades arc in this region, the post-arc lavas are primarily tapping a lithospheric mantle source, but for the TTVF, melting is triggered by asthenospheric upwelling around the south edge of the Juan de Fuca slab. TTVF lavas include a much lower proportion of melts from the (now, ex-) mantle wedge, since slab fluids are no longer supplied to the mantle beneath this region. The lithospheric mantle source in the TTVF may be similar chemically and mineralogically to that of the Big Pine volcanic field and Long Valley caldera in the Western Great Basin. This example of slab window volcanism is unusual in that the lavas are not melts of a mantle source that is more depleted in incompatible elements than the arc source. © 2010 Elsevier B.V.